PENDUGAAN CADANGAN KARBON PADA TANAMAN BAMBU TALANG (Schizostachyum brachycladum Kurz.) DI HUTAN RAKYAT BAMBU DESA PERTUMBUKAN KECAMATAN WAMPU KABUPATEN LANGKAT - Hafizah Arinah; Muhdi Muhdi; Irawati Azhar (Program studi Kehutanan USU, 2016)
The Chlorophyll vegetation is able to absorb CO2 from the atmosphere through photosynthesis, as well as the bamboo talang does. The purpose of this research was to account the carbon content in each section of bamboo talang (Schizostachyum brachycladum kurz.) and to determine the best allometric model to estimate the potential of carbon reserves in the bamboo talang in harvested-over areas in people forest bamboo, Village Pertumbukan. The research was carried out in two stages, namely the first stage was to take the data in the field and the second stage was to analyze the carbon content in each section of bamboo talang in the laboratory. The results showed that the best allometric model for estimating biomass and carbon mass of bamboo talang was W = 44.614-14.047D+1.26D2 and C = 20.159-6.390D+0.585D2. Biomass and carbon mass off bamboo talang in People Forest Bamboo Pertumbukan Village, District Wampu, Langkat were 5.85 ton/ha and 2.82 ton C/ha, respectively. Keywords: Bambu talang (Schizostachyum brachycladum Kurz)., community forest, carbon stock, allometric models